EDUCATORS' STRATEGIES IN IMPLEMENTING TOLERANCE VALUES TO ANTICIPATE NEGATIVE BEHAVIOR AT THE ELEMENTARY SCHOOL LEVEL - Annisya Anggreiny; M. Daffa Diyah Ulhaq; Neng Sarah Aprilia; Yurma Vadelta (Journal of Pedagogical Content Knowledge, 2026)
This study aims to analyze the phenomenon of bullying among elementary school students, including its forms, contributing factors, impacts, and prevention strategies that can be implemented in the school environment. Bullying is a significant issue in elementary education because it can negatively affect students’ psychological well-being, social relationships, participation in learning, and academic development. Bullying may occur in various forms, including physical, verbal, relational, and social behaviors, such as hitting, mocking, threatening, excluding, humiliating, or deliberately isolating peers. Several factors may contribute to the occurrence of bullying, including inadequate supervision from parents and teachers, unfavorable family environments, lack of empathy and social awareness, peer influence, and the normalization of aggressive behavior within the surrounding environment. The consequences experienced by victims may include reduced self-confidence, fear, anxiety, social withdrawal, decreased motivation to learn, and difficulties in maintaining healthy relationships with peers. In more serious and prolonged cases, bullying may have lasting effects on students’ psychological and social development. Therefore, schools have an important responsibility to establish comprehensive and sustainable bullying prevention programs. Preventive efforts can include strengthening character education, developing students’ empathy and social skills, establishing clear anti-bullying policies, improving teacher supervision, providing safe channels for reporting incidents, and conducting guidance and counseling activities. Parental involvement is also essential to ensure consistency between education at school and support at home. The study concludes that effective bullying prevention requires collaboration among schools, teachers, parents, students, and the wider community. Through a safe, inclusive, and supportive educational environment, schools can reduce bullying behavior and support the optimal social, emotional, and academic development of elementary school students.